Capital Punishment in the Perspective of the National Criminal Code and the Kutaramanawa Dharmasastra Majapahit - Utami, Tanti; Nurhakiki, Ahmad; Ramadhan, Muhammad; Mulyana, Moch; Hikmat, Muhammad (Indonesian Journal of Law and Justice, 2025)
This study aims to analyse the comparison of capital punishment regulations in the latest National Criminal Code (KUHP) and the Kutaramanawa Dharmasastra from the Majapahit Kingdom era, where this study is important for understanding how the concept of the death penalty has undergone a transformation from a traditional legal system steeped in religious and cosmological values to a modern legal system that places greater emphasis on the protection of human rights, the principle of justice, and strict legal procedures. Thus, this study not only compares legal norms but also traces the paradigm shift in justice and the values behind it. The research method used is a normative legal method with a legislative and historical approach, where the legislative approach is used to examine the provisions on capital punishment in the 2023 Criminal Code, while the historical approach is used to trace the practice and philosophy of the application of capital punishment during the Majapahit era as reflected in the Kutaramanawa Dharmasastra. This research is descriptive-analytical in nature, relying on secondary data from legislation, classical law books, academic literature, and previous research results. The results of the discussion show that there is a fundamental difference in the orientation of criminal law, where in the Kutaramanawa Dharmasastra, the death penalty is positioned as the main punishment imposed for various serious crimes in order to maintain the political and cosmological stability of the kingdom, whereas the National Criminal Code places the death penalty as a special, conditional alternative punishment oriented towards the principle of ultimum remedium. This shift shows the direction of Indonesian criminal law reform, which is more cautious, humanistic, and in line with human rights principles, even though debates regarding its effectiveness and fairness are still ongoing.